Growing PAUD Teacher Creativity Through Creative Play Activities - Lilis Suryani; Nita Adiyanti; Mila Wahyuni; Ilah Carilah; Ilis Kandarisah (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Early childhood children are very interested in creative and unique learning media. Teacher creativity in this matter is really needed. It is hoped that the importance of creative play in children can be fulfilled through school. However, in reality teachers are still fixated on the curriculum prepared by the government but there is a lack of development in learning applications. Apart from that, the facilities provided by schools to create creative learning media are still limited. The aim of holding this training is to develop the potential and creativity of teachers so that learning at school becomes interesting. This training was carried out at the Creative Center Building, Purwakarta Regency on 11 May 2024 and in Tegalwaru District, Purwakarta Regency on 18 May 2024. The results obtained by educators can be applied through creative play in learning activities. Based on the results obtained, it is known that the average pre-test result is 70. Meanwhile, the average post-test result is 87. Thus, it can be concluded that there has been an increase in the competency capacity of training participants before and after participating in the training by 17%. These results are input for various stakeholders, especially intuitions that oversee the institutions that are training participants in this program.